Cannabinoid medicine in the orofacial region: status and prospects - Mederos, Matias (2023)
Introduction: The interest in using cannabis and cannabinoids as a therapeutic tool has gained relevance in medicine in recent years. In line with this, interest in its study has increased in dentistry. The aim of the present narrative review was to analyze and synthesize the available information about the current therapeutic possibilities of cannabis in dentistry and its future perspectives. Materials and methods: an electronic search conducted that included articles until December 2022, in the MEDLINE, Scopus, Scielo and Google Scholar databases. The following main keywords used: “dental,” “dentistry,” “cannabis,” “cannabinoids,” “benefits,” “therapeutics,” “treatment,” “potential.” A total of 834 records founded in the first searches. Forty-five full-text articles assessed for eligibility. Thirty-five studies included for the qualitative analysis of the present review. Results: Studies show a great variability of cannabinoids and derivatives used, including commercial preparations, as well as experimental preparations. In vitro, in vivo, and clinical studies had conducted evaluating the action of cannabinoids in the control of orofacial pain, as anti-inflammatory and healing, in bone tissue regeneration, as antimicrobial and evaluating their anti-cancer ability. Conclusions: Cannabinoids have shown potential in the treatment of various oral conditions and/or disorders. Even the standardization of products and treatment protocols is insufficient, which is why more studies are necessary to evaluate presentations, derivatives, extraction methods, concentrations, and routes of administration for their best use.